A CONCEPTUAL ANALYSIS OF CIVILIAN CONTROL OF THE NIGERIAN MILITARY UNDER DEMOCRATIC DISPENSATIONS - MOHAMMED LAWAL TAFIDA (International Studies Journal)
A central question in civil-military relations literature is on how civilian control of the military takes place in a State. In this respect, the challenge in instituting such control exists in a country that has at different times experienced both military and civilian governments. Since independence, Nigeria has so far witnessed three civilian dispensations- the First, Second and On-going Fourth Republics. In these periods, the military was under the control of civilian-led parliamentary and presidential democracies. This paper conceptualises the nature of civilian control of the military in these dispensations by assessing the frameworks, challenges and outcomes. Using liberal-democratic prescriptions that define civilian control as conceptual framework, it employs the historical, constitutional, structural and institutional approaches as analytical tools. The paper argues that despite the existence of constitutional provisions, structural weaknesses inherent in democratic institutions of these dispensations have affected the nature, basis and outcomes of civilian control of the military.